2015
DOI: 10.1080/01694243.2015.1062653
|View full text |Cite
|
Sign up to set email alerts
|

One-step fabrication of superhydrophobic and superoleophilic cigarette filters for oil-water separation

Abstract: To develop a simple and efficient way to recycle used cigarette filters, we report on a one-step method for preparing superhydrophobic and superoleophilic cigarette filters for oil-water separation. The robust coating layer on the surface of the cellulose acetate fiber, along with the inherent rough texture of the cigarette filter, could lead to its surface that displayed superhydrophobicity and superoleophilicity. Water droplets can retain in spherical shapes on the modified cigarette filters, while oils were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The fabrication process for the adsorbent started with the collection and cleaning of the filters before shredding. The shredded cigarette filters were soaked in ethanol under utrasonication for 1 h to remove impurities, and were subsequently hydrolysed in 1 molar sodium hydroxide solution for 10 min to enhance the roughness of the surfaces of the filters [18]. The filters were washed in distilled water until the supernatant was clear.…”
Section: Fabrication Of Adsorbentmentioning
confidence: 99%
“…The fabrication process for the adsorbent started with the collection and cleaning of the filters before shredding. The shredded cigarette filters were soaked in ethanol under utrasonication for 1 h to remove impurities, and were subsequently hydrolysed in 1 molar sodium hydroxide solution for 10 min to enhance the roughness of the surfaces of the filters [18]. The filters were washed in distilled water until the supernatant was clear.…”
Section: Fabrication Of Adsorbentmentioning
confidence: 99%
“…In the research by Ou et al, used CF was modified by hexadecyltrimethoxysilane to clean up oil spills on water [5]. Liu et al reported a superhydrophobic and superoleophilic CF modified by octadecyltrichlorosilane for oil-water separation [32]. In this study, we report a simple and environmentally friendly method for preparation of superhydrophobic CF via methyltrimethoxysilane (MTMS) and octadecyltrichlorosilane (OTS) and the application for oil-water separation.…”
Section: Introductionmentioning
confidence: 95%
“…Cellulose not only has good biodegradability and biocompatibility, but also has excellent thermal and chemical stability [21,22]. Many materials derived from fibers have been used for oil-water separation, for instance, cellulose polyesters [23,24], cellulose acetate [25,26], organogelator-cellulose [27], cellulose aerogels [28,29], cotton [30], paper[31] and CF [5,32]. Here, our goal is to transform CF into a superhydrophobic absorbent that can be repeatedly used for removal of spilled oils from water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If cigarette filters can be used as an oil/water separation material, this can effectively solve the problem of the difficult recycling and degradation of waste cigarette filters. In the research process, we found that there are few cases of oil/water separation in the field of cigarette filter recycling [26][27][28]. The polymerization of silane coupling agents is the main method used in the literature to prepare superhydrophobic cigarette filters.…”
Section: Introductionmentioning
confidence: 99%